Comparison of the chemopreventive potentials of melatonin and vitamin E plus selenium on 7,12-dimethylbenz[a]anthracene-induced inhibition of mouse liver antioxidant enzymes - Batcioglu, K; Karagözler, AA; Genç, M; Çelik, S (Lippincott Williams & Wilkins, 2002)
Chemoprevention is a rapidly growing area of oncology that is identifying agents with a potentially preventive role in cancer. In this study, it was our goal to compare the chemopreventive effects of vitamin E plus selenium, and melatonin. Forty female mice were divided into four equal groups. The first group served as control. The second group had i.p. injections of 7,12-dimethylbenz[a]anthracene (DMBA) (20 mg/kg body weight) in corn oil for 21 days. The third group had the same procedure of DMBA injections as the second group and received vitamin E + selenium (90 mug + 1.8 mug/day), simultaneously. The fourth group had DMBA injections and melatonin (4.2 mg/kg body weight), simultaneously. DMBA alone caused significant inhibition of hepatic glutathione peroxidase (GSHPx), catalase (CAT), and superoxide dismutase (SOD) in the second group. In the third group, vitamin E + selenium restored DMBA-induced GSHPx inhibition significantly whereas CAT and SOD inhibition remained essentially unchanged. In the fourth group, melatonin not only significantly decreased DMBA-induced GSHPx inhibition but also fully reversed CAT and SOD inhibitions caused by DMBA. We speculate that melatonin alone provides better chemoprevention against DMBA-induced oxidative stress than the vitamin E + selenium combination. (C) 2002 Lippincott Williams Wilkins.
Keywords: chemoprevention; DMBA; melatonin; selenium; vitamin E